The Concept of God in the Divine-logic of Mark’s Gospel - ZHA, Changping (Journal of Research for Christianity in China (JRCC), 2022)
After this paper discusses the significance of the gospel in the Divine-logic of Mark’s Gospel, it treats with the concept of God who is an eternally living, Father in heavens and almighty one. In Mark’s mind, He is also God in the Kingdom of God, belongs to that of Jesus disciple’s community. Mark’s Gospel, therefore, gives a basis of the theology of earlier Christianity. It is worthy for Sino-theology today to delve into this Gospel.